Usability of mHealth in Patient with Type 1 and Type 2 Diabetes Mellitus: A Review - Belinda, Andhara M.; Milanda, Tiana (Universitas Padjadjaran, Indonesia, 2023)
Diabetes mellitus (DM) is a group of metabolic illnesses identified by elevated blood glucose levels. The glycated hemoglobin (HbA1C) test is used to evaluate a person’s control of their blood glucose levels. According to a recent study, mHealth interventions may be particularly helpful for assisting patients with diabetes mellitus to self-monitor their status on their HbA1c level. Therefore, this systematic review aims to provide an overview of how mHealth affects individuals with diabetes mellitus, concentrating on HbA1c evaluation. A systematic review was conducted by reviewing the PubMed, Google Scholar, and Mendeley databases for randomized control trials published between February 2017 and September 2023. The studies of mHealth on the result of HbA1c were then examined. A drop in HbA1c was seen in all intervention groups. The overall average reduction in HbA1c across all intervention groups was - 0.79%, while the reduction in control groups was - 0.42%. The influence of mHealth could significantly reduce HbA1c levels. Studies show that HbA1c decreased more in patients who underwent a 3 to 6-month intervention. This study discovered 12 papers that discuss health for people with diabetes mellitus type 1 and 2. This study found that mHealth interventions significantly lower HbA1c in DM patients. For further research, bigger sample sizes and data on self-care results are needed. The views and perspectives of patients regarding the physical characteristics and design aspects of different interventions—mobile applications, texts, and phone calls—need to be further investigated.